Bronchopulmonary Nematodes in Alpine Ibex: Shedding of First Stage Larvae Analyzed at the Individual Host Level - Zanet, Stefania; Ferroglio, Ezio; Orlandini, Filippo; Bassano, Bruno; Battisti, Elena; Brambilla, Alice (Frontiers in Veterinary Science, 2021)
Pneumonia is the most frequent cause of death for Alpine ibex (Capra ibex) in Gran Paradiso National Park, (Italy). The aetiology of this form of pneumonia is currently unknown and the identification of the primary etiological agent remains difficult due to biological and logistic constraints. Uncovering individual differences in Protostrongylid prevalence and intensity is important to further investigate the epidemiology of respiratory diseases and their relationship to heterozygosity and inbreeding in a once almost extinct population like C. ibex. In a group of 21 individually recognizable adult male we monitored prevalence and intensity of Protostrongylid first-stage larvae using Baerman’s technique from June to September 2019. First-stage larvae of 5 genera were detected. Muellerius (P=100%, CI95%= 84-100) and Protostrongylus (P=86%, CI95%:71-100) were two dominant genera according to Bush’s importance index. Neostrongylus (P=38% ,CI95%: 17-59), Cystocaulus (P=33% ,CI95%= 13-53) were classified as co-dominant genera while Dictyocaulus filaria (P=0.05%, CI95%=0.04-0.13) was detected, for the first time in Alpine ibex, in one subject. Larval excretion varied significantly over time, with minimum L1 excretion in July. Individual median larval intensity ranged from 4.4 lpg to 82.2 lpg with Poulin’s discrepancy index showing highly aggregated distribution patterns for Muellerius spp. (D=0.283, CI95%= 0.760-0.895) and Protostrongylus spp. (D=0.635, CI95%= 0.580 - 0.705). Presented data provide the necessary base point to further investigate how lungworm infection account for the different rates of progression of pneumonia in C. ibex. Individual aggregation of larval intensity must be further evaluated to determine whether these differences mirror different levels of parasitic infection related to individual differences in immune response, hormonal-states or genetic fitness.